Death as ‘the only certainty’ - Souza Camargo, Roberto; de Souza Filho, João (O Mundo da Saúde, 2012)
The present paper had is based on results of a long observation period and behavioral perception of several servants of the Legal Medical Institute of Sao Paulo (IML), during the period of professional contact with these servants and the event of death, a period of experience of nearly 35 years for each author, which were in daily contact with the setting of the most varied unities of IMLs in the condition of forensic scientists. For doing this, we propose as a reflection around this central subject the questions: how near is a “Death Worker” with death?; what really does torment the psychological state of the worker dealing with death?; what produces the dilemma and creates trauma? We concluded that it is necessary to make this servant to face the reality in which they live, without getaways or masks, demonstrating their relevant contribution to society.